The Impact of Parental Earnings and Education on the Schooling of Children - O'SULLIVAN, VINCENT (University College Dublin, 2011)
This paper addresses the intergenerational transmission of education and investigates the extent to which early school leaving (at age 16) may be due to variations in parental background. An important contribution of the paper is to distinguish between the causal effects of parental income and parental education levels. Least squares estimation reveals conventional results ? weak effects of income (when the child is 16), stronger effects of maternal education than paternal, and stronger effects on sons than daughters. We find that the education effects remain significant even when household income is included. However, when we use instrumental variable methods to simultaneously account for the endogeneity of parental education and paternal income, only maternal education remains significant (for daughters only) and becomes stronger. These estimates are consistent across various sets of instruments. The impact of paternal income varies between specifications but becomes insignificant in our favored specifications. Our results provide only limited support for policies that alleviate income constraints at age 16 in order to alter schooling decisions. In contrast, our results do suggest that policies which increase permanent income would lead to increased participation (especially for daughters).
PUBLISHED
Keywords: Education; Parental Income